Chemosystematic of Enterobacteriaceae Familia Obtained from Blood Cultures Based on Total Protein Profiles - Sri Darmawati; Langkah Sembiring; Widya Asmara; Wayan T. Artama; Syaiful Anwar (Indonesian Journal of Biotechnology, 2013)
The purpose of this study was to determine the chemosystematic of 14 strains of bacteria in blood cultures from Semarang using 1 reference strain S. typhi NCTC 786, based on the total protein profi les with the similarity relationship analysis based on Simple Matching Coeffi cient (SSM) analysis and algorithm methodof unweighted pair group with averages (UPGMA) presented in a dendrogram. The results showed that thechemosystematic based on the total protein profi les using SDS-PAGE method can classify the member ofbacterial strains of each species. The Clusters respectively consist of 4 strains of S. typhi (similarity: 89.7%),2 strains of Ser. marcescens (similarity: 89.7%), two strains of E. coli, and one strain of Salmonella ssp, S. typhi NCTC 786 (similarity: 100%). Those three incorporated clusters had the similarity value of 75.3%. Those four strains of Ent. cloacae composed in one cluster (similarity: 100%) are incorporated in a cluster consisting of one strain of Kleb. pneumoniae (similarity: 92.9%). Both clusters were incorporated in a cluster consisting of S. typhi NCTC 786 (similarity: 67.9%). Key words: Enterobacteriaceae, chemosystematic, blood cultures, protein profile